The First English-speaking Community : Global Development Plan 2004-2009 - Grundy, Susan (Quebec Community Groups Network (QCGN), 2003)
The English-speaking Community of Quebec (ESC) represents multiple communities that are diverse, multicultural and multiracial in nature. The Community includes English-speakers who choose to speak or use the English language, for example, for delivery of services. The Community also includes those citizens who identify with, or have an interest in, the English language. The first step taken by the Global Development Planning Steering Committee was to review the need for a Plan to revitalize the English-speaking Community of Quebec. Why are we doing this? Is a Global Development Plan necessary? What do we hope to achieve?

Global Development Plan 2004-2009 : Revitalizing the English-speaking Communities of Quebec - Quebec Community Groups Network (QCGN) (2003)
The English-speaking Community of Quebec (ESC) represents multiple communities that are diverse, multicultural and multiracial in nature. The Community includes English-speakers who choose to speak or use the English language, for example, for delivery of services. The Community also includes those citizens who identify with, or have an interest in, the English language. The first step taken by the Global Development Planning Steering Committee was to review the need for a Plan to revitalize the English-speaking Community of Quebec. Why are we doing this? Is a Global Development Plan necessary? What do we hope to achieve?

President's Report on Highlights of Activities Representing QCGN : June 2002 - June 2003 - Murphy, Martin P. (Quebec Community Groups Network (QCGN), 2003)

Quebec Community Groups Network : Executive Director's Report 2002-2003 - Hook, Deborah (Quebec Community Groups Network (QCGN), 2003)
The year 2002-2003 has once again been an exciting year of growth and deveiopment for the QCGN. Through the many activities undertaken over the past year, we have re-enforced the solidarity among our members and extended our outreach past the QCGN membership into the broader English-speaking community of Quebec.

Quebec Community Groups Network By-Laws - Quebec Community Groups Network (QCGN) (2003)

Global Development Plan : Strategy to Revitalize the English-language Minority Communities of Quebec : Sector Plans - Quebec Community Groups Network (QCGN) (2003)
The roots of the English-speaking community in Quebec go back nearly 250 years, and have a historic place in the development of the province. While English-speaking communities traditionally established their own institutions in the areas of religion, education and health and social services, that type of community engagement dissolved to a greater extent with the Quiet Revolution and the emergence of the modern Quebec state. Now, after 30 years of exodus and isolation, the time has come for the English-speaking community to become involved, to re-establish its presence in the policy and program decision-making areas that affect the daily lives of its members.

Global Development Plan : Strategy to Revitalise the English Language Minority Communities of Quebec : Arts & Culture Plan - Quebec Community Groups Network (QCGN) (2003)
The Global Development Plan initiative originates from a request of the Federal Government to develop a funding framework. The GDP represents an opportunity for the English-speaking community to take charge of its current stage and identity within Quebec. This would include developing a clearer picture of the English-speaking population of Quebec, where it comes from and where it's going; helping maintain the population base by encouraging a sense of belonging; raising the profile and participation level of English-speaking people at the municipal, institutional and govemment levels; promoting employment opportunities within the community for English speaking youth; initiating community projects; and maintaining dialogue with governments in the francophone community.

Global Development Planning : Strategy to Revitalise the English Language Minority Communities of Quebec : Education & Training - Quebec Community Groups Network (QCGN) (2003)
The following Plan has been prepared by the Education & Training Task Force - one of eight sector task forces which bring together leading representatives from across the Province committed to the preparation of a Global Development Plan for the Englishspeaking minority communities of Quebec.